(untitled) (ResearchJet Journal of Analysis and Inventions, 2022)
The forming of students’ environmental culture in educational field of a university is displayed. The formation models of moralandaesthetic components of the environmental culture are presented, the content of units and modules is disclosed. Fragments of the author’s programme of the environmental and educational projects are given.